Genetic alterations shaping tumor response to anti-EGFR therapies. (September 2022) - Vaquero, Javier; Pavy, Allan; Gonzalez-Sanchez, Ester; Meredith, Mark; Arbelaiz, Ander; Fouassier, Laura
Abstract: The Epidermal Growth Factor Receptor (EGFR) has been targeted through the development of selective tyrosine kinase inhibitors (TKIs) and monoclonal antibodies (mAb). These molecules have shown effectiveness in a subset of patients with specific genetic alterations (i.e. gain-of-function EGFR mutations or EGFR gene amplification) and have been approved for their use in non-small-cell lung cancer (NSCLC), colorectal cancer (CRC), pancreatic cancer and head and neck cancer. In addition, extensive research is being performed in many other tumour types hoping for a future approval. However, the majority of the patients show no benefit from these molecules due to primary mechanisms of resistance, already present before treatment or show disease progression upon the acquisition of drug resistance mechanisms during the treatment. At present, the majority of patients display resistance due to alterations in genes related to the EGFR signalling pathway that eventually circumvent EGFR inhibition and allow cancer progression. Thus, in this review article we focus on the molecular mechanisms underlying drug resistance via genetic alterations leading to resistance to all anti-EGFR drugs approved by the FDA and/or EMA. We also discuss novel approaches to surmount these chemoresistance modalities.